Africa in international relations: The frontier as concept and metaphor - (:unkn) unknown (My University, 2013)
The concept of the frontier has often been used to account for the rise of Africa in international relations and the world economy over the past decade. It is argued that, from a more general standpoint, the association of the frontier with a diversity of interpretations offers a useful tool to monitor the narratives, policies and trajectories associated with the African continent since the end of the Cold War. The article first examines Africa's international relations through the metaphors of a 'distant abroad' and a 'significant other', before discussing the notions of a new frontier and a global interface. In the latter case, the concept helps to make sense of critical issues and transitions. It is argued that the current revival of interest in Africa is associated with two broad scenarios for the continent: on the one hand, the deepening of Africa's insertion within the world economy through increasing dependency on commodities; on the other, a pattern of innovative policy-initatives and processes that offer a contemporary expression of the emerging economies paradigm.
Keywords: African Research